Disinfection:A View from the Early 21st Century - Bal, C; Hoffman, PN; Rotter, ML (International Journal of Infection Control, 2009)
The origins of today’s disinfection practices go back tothe 19th century. Although we have learned much sincethen, there are still gaps in our knowledge; gaps both intheory and in the practical application of disinfection.This collection of three short papers is taken from asession at the 6th Congress of the International Federationof Infection Control held in Istanbul, Turkey in October2005. It provides an overview of the current status ofdisinfection, as well as an assessment of possible problemsyet to come.